Abstract 27 Limitations of Current Human Cell, Tissue, and Cellular-based Product Donor Eligibility Guidance: Analyzing the Impact on a Large Public Cord Blood Bank. (6th September 2022) - Guggenheim, Dana S; Kurtzberg, Joanne; Shaz, Beth
Abstract: Introduction: Cord blood (CB) is considered a human cell, tissue, and cellular-based product (HCT/P) by the U.S. Food and Drug Administration (FDA) and is licensed through a Biological Licensing Application (BLA). Cord blood units (CBUs) require less precise donor tissue matching than other stem cell sources, which increases their availability for racial/ethnic minorities. However, a small percentage of banked CBUs are used for transplants. Updating FDA donor eligibility guidance may expand licensed CBU supply and cord blood bank (CBB) sustainability. Objective: The objectives of this study were to analyze the impact of Zika virus (ZIKV) donor screening recommendations on the licensing status of banked CBUs and to propose updated policy recommendations. Methods: A retrospective analysis of Carolinas Cord Blood Bank (CCBB) data (from January 2016 to May 2022) was performed to describe CBU eligibility and shipment status. Qualitative comparisons of FDA guidance to reduce the risk of relevant communicable diseases were completed for blood versus HCT/P. Results: CCBB: 8, 877 banked CBUs from 2016-2022 (85.3% licensed; 14.7% unlicensed) (Table 1). 4, 361 (49.1%) of CBUs were from Caucasian donors and 1, 349 (15.2%) were from African American donors. 689 (52.7%) CBUs were unlicensed due to ZIKV risk. The number of CBUs with ZIKV risk banked annually has decreased significantly since 2020, with 174 ZIKV-risk CBUs in 2020 versus 63 in 2021. 26 unlicensed CBUs collected in 2016 or later have been infused versus 210 licensed CBUs. 7 unlicensed, infused CBUs had identified ZIKV risk. No ZIKV transmission was reported from these transplants. FDA Guidance: HCT/P ZIKV recommendations have not been updated since 2018 despite FDA removal of ZIKV from the relevant transfusion-transmitted infections in 2021. Recommendations for minimizing transfusion-transmission risk of human immunodeficiency virus (HIV) and variant Creutzfeldt-Jakob disease (vCJD) were updated in 2020 and 2022, respectively, to increase blood supply. New vCJD guidance eliminated geographic risk-related donor restrictions. Discussion: Guidance for reducing disease transmission for blood and blood components have recently been updated to increase blood supply. The FDA must consider new data to revise the HCT/P donor screening recommendations. Adopting these changes will increase the number of HCT/P donors, the quantity of licensed CBUs, and potentially improve access to cellular therapies for a more diverse patient population.